Nursing theorists and their work - Alligood, Martha Raile; Marriner-Tomey, Ann , 1943- (Maryland Heights, Missouri : Mosby/Elsevier, 2010)
Offers a look at 49 theorists of historical, international, and significant importance. This book includes case studies and critical thinking activities that help bridge the gap between theory and application
1. Evolution of Nursing theories -- 2. Philosophies -- 3.Nursing models -- 4. Nursing theories -- 5. Middle range theories -- 6. Future of Nursing theory
Previous ed.: published as edited by Ann Marriner Tomey, Martha Raile Alligood. St. Louis, Missouri; London: Elsevier Mosby, 2005
Includes bibliographical references and index
Keywords: Nursing models; Nursing -- Philosophy; Nursing Theory; Models, Nursing; Nurses -- Biography; Philosophy, Nursing